Lung cancer - Roth, Jack A.; Hong, Waun Ki.; Komaki, Ritsuko (Hoboken, New Jersey : John Wiley & Sons, 2014)
Lung Cancer is a comprehensively revised and expanded edition the well-established, concise, multidisciplinary reference book dealing with advances in lung cancer clinical research and treatment for the clinician. Edited and authored by leading authorities in the field, it is the best concise single source for state-of-the-art diagnosis and treatment of lung cancer. The new fourth edition is now better than ever, incorporating the most recent work in the field of lung cancer research, diagnosis, and treatment. This book has always been well known and highly regarded for its concise presentations.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Lung Neoplasms -- diagnosis; Lung Neoplasms -- therapy; Lungs -- Cancer; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Lungs -- Cancer; Electronic books